Gaining an Understanding of DevOps from its Enablers to Its Impact on Performance - Bhardwaj, Arvind Kumar; Rangineni, Sandeep (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Despite these efforts’ merit, academics have had trouble keeping up with the radical shifts in how software is created and supplied to clients. DevOps has revolutionized the way IT businesses are intended to operate as the result of years of hard effort and improvement to software delivery methods, techniques, and philosophies. Despite its widespread use and the positive effects, it has had on IT businesses’ bottom lines, few people outside of the industry really understand what it is, how it operates, or if it can genuinely lead to better IT performance. This study provides a methodology that bridges the gap between these macro-level elements and the actual results of IT departments by focusing on the enabling components of DevOps, such as technological and management skills, and IT culture. Moreover, this study suggests the values of a perfect DevOps organization, which have a profound impact on IT Outcomes when they are in harmony with the firm’s Delivery Approach. Information technology (IT) experts with prior DevOps experience were used to compile the survey results. In all, 176 American respondents provided their information. This alignment, in turn, has a substantial impact on IT Outcomes. This study adds not only to the growing body of literature on DevOps and software delivery, which is essential to the success of any IT firm, but also to the development of important underlying theory in these areas.